Impact of the COVID‐19 pandemic on interventional cardiology training in the United States. Issue 5 (26th August 2020) - Shah, Samit; Castro‐Dominguez, Yulanka; Gupta, Tanush; Attaran, Robert; Byrum, Graham Vance; Taleb, Adam; Pettyjohn, Amanda; Bartel, Robert C; Szerlip, Molly; Henry, Timothy D.; Mahmud, Ehtisham; Applegate, Robert J
Abstract: Objectives: We sought to determine the effect of COVID‐19 related reduction in elective cardiac procedures and acute coronary syndrome presentations on interventional cardiology (IC) training. Background: The COVID‐19 pandemic has significantly disrupted healthcare in the United States, including cardiovascular services. The impact of COVID‐19 on IC fellow training in the United States has not been assessed. Methods: The Society for Cardiovascular Angiography and Interventions (SCAI) surveyed IC fellows training in both accredited and advanced non‐accredited programs, as well as their program directors (PD). Results: Responses were received from 135 IC fellows and 152 PD. All respondents noted reductions in procedural volumes beginning in March 2020. At that time, only 43% of IC fellows had performed >250 PCI. If restrictions were lifted by May 15, 2020 78% of IC fellows believed they would perform >250 PCI, but fell to only 70% if restrictions persisted until the end of the academic year. 49% of IC fellows felt that their procedural competency was impaired by COVID‐19, while 97% of PD believed that IC fellows would be procedurally competent at the end of their training. Most IC fellows (65%) noted increased stress at work and at home, and many felt that job searches and/or existing offers were adversely affected by the pandemic. Conclusion: The COVID‐19 pandemic has substantially affected IC training in the United States, with many fellows at risk of not satisfying current program procedural requirements. These observations support a move to review current IC program requirements and develop mitigation strategies to supplement gaps in education related to reduced procedural volume.